Invasive mold infections in lung and heart‐lung transplant recipients: Stanford University experience. Issue 2 (April 2015) - Vazquez, R.; Vazquez‐Guillamet, M.C.; Suarez, J.; Mooney, J.; Montoya, J.G.; Dhillon, G.S.
Abstract: Background: Recipients of lung transplantation (LT) and heart‐lung transplantation (HLT) are at increased risk of infection, including invasive mold infections (IMIs). The clinical presentation, radiographic correlates, and outcomes of Aspergillus and non‐ Aspergillus IMIs in this population have not been well documented. Methods: LT and HLT recipients diagnosed with IMIs between 1990 and 2012 were identified using the Stanford Translational Research Integrated Database Environment and Stanford LT and HLT clinical database. Recipient clinical and radiographic characteristics were obtained via retrospective review of medical records and compared between Aspergillus and non‐ Aspergillus mold recipients. Risk factors for mortality were identified using multivariate logistic regression analysis. Results: During the study period, 87 (14%) transplant recipients were diagnosed with IMIs. Aspergillus species were isolated in 63 (72%) and non‐ Aspergillus molds in 24 (28%) recipients. No significant difference was seen in presenting symptoms or radiographic findings between Aspergillus and non‐ Aspergillus mold recipients. Median time to diagnosis was 363 days in the Aspergillus group and 419 days in the non‐ Aspergillus group, with dissemination occurring only within the non‐ Aspergillus group (12.5%). Overall 90‐day and 1‐year mortality following IMI was 24% and 44%. One‐year mortality was increased in the non‐ Aspergillus group (39.5% vs. 60.5%, P = 0.03). Conclusions: There is significant overlap in risk factors, presentation, and radiographic patterns in IMI in LT or HLT recipients. Non‐ Aspergillus molds were more likely to present late, with disseminated disease, and portend increased 1‐year mortality.